DRUG COST ANALYSIS ON NATIONAL HEALTH INSURANCE ERA IN HEALTH SUPPORT FACILITIES - Satibi, Satibi; Putu Satrya Dewi, Dewa Ayu; Akhmad, Atika Dalili; Kaswindiarti, Novita; PUSPANDARI DA (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: In national health insurance (JKN) era, pharmacy can play roles in the form of behind refer pharmacies, or networking pharmacy and clinic pharmacy pratama. Behind refer pharmacies drug cost can be claimed directly to BPJS, meanwhile for the other type of pharmacy have to negotiation first with the primary health care. Drug cost variations in the JKN era affect the profitability of the business pharmacies. This research aims to the drug percentage charges against capitation and variety of drug costs. Methods: This research is analytic observational cross-sectional. This research uses secondary data from a JKN prescription patient. This research was conducted on 6 affiliated pharmacies, 6 networking pharmacies, and 7 clinical pharmacy pratama in DIY. The sampling in this research is by purposive with 8.430 prescriptions. Data drug costs JKN era was analyzed by descriptive statistics and comparative test (Kruskal Wallis test). Results: The result showed that average percentage of drug costs for capitation fee in the networking pharmacy is 13.58% and primary health care is 15.91%. Pharmacy in JKN era has drug cost variations (p=0.000). Drug cost in JKN era depends on the pattern of play roles with the health facilities and BPJS. The average percentage of drug costs against capitation health facilities in networking pharmacy is lower than clinical pharmacy pratama. Conclusions: Drug costs in an era of JKN depending on the pattern of cooperation with health facilities pharmacies and BPJS. The average percentage of the cost of drugs to the pharmacy capitation health facilities in networking lower than clinic pharmacy pratama. Differences in drug costs JKN era influenced by the long days of drug administration, the number of prescription sheets, margin. Keywords: Drug cost analysis, National health insurance (JKN), Pharmacy, Primary health care, Capitation.